An experimental investigation of the “fate” of entrained peritectic minerals during adiabatic ascent of S-type granite magmas - Mthethwa, Mbali Pertunia (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.